(untitled) (Eurasian Journal of Philology Science and Education, 2026)
The cult of the wolfwas spread in many nationsas a figure of strong, freedom beast, which cannot be broken and tame. In the ancient Turks and Mongols the wolf was the main totem that was esteemed as the progenitor. Figure of the Heavenly Wolf runs through the ditch narrativeof the ancient monument of writing «Oguz-name.» Image of the wolf in our literature has not previously been the subject of special study, but it is being addressed in general works, considering the traditional culture of the Kazakhs. Analysis of papers, devoted to the consideration of the symbolism of the wolf, suggests that the study of this question in the Kazakh literature is fragmented or highly specialized character. With the emergence of new scientific methods of research the rich folklore and myth epicmaterials of Kazakh traditional culture which concerned the symbol of wolf, needs a deeper consideration of this issue. As a result of the typological and genealogical relation we have established that the wolf in «Oguz name» is endowed with a double zooantropomorfic nature to jut out at the same time as a form of a man and as a form of an animal. Comparative analysis allowed us to conclude that wolf as a holy animal very admired by Turks, and the echoes of admire have survived to this day in the legends and tales.